PEMETAAN SARANA DAN PRASARANA PERMUKIMAN DI KAMPUNG WASUR - Chitra Utary; Budi Doloksaribu; Dewi Sriastuti Nababan (Musamus Devotion Journal, 2020)
Wasur Village is a village that has been equipped with various facilities and infrastructure. With the existence of village facilities and infrastructure, both the existence of maps is available that can be seen by local people and people from outside the village. The purpose of community service activities with training in settlement arrangements and infrastructure in Wasur village is one of the efforts to improve Kampung apparat's human resources in making locations and infrastructure using simple applications. In making this, it is done first by installing the existing facilities and infrastructure, then the village facilities and infrastructure are made using the application. The results obtained from this activity are village apparatuses that can apply the knowledge that has been channeled on the authority of the village that can implement it by making a map of facilitation and residential infrastructure in Kampung Wasur.